Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/1540-627x.00066
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Behavior, Entrepreneurial Style, and Small Firm Performance

Abstract: Considerable effort has been devoted to identifying the general characteristics of entrepreneur; however, much of this has been conducted from a trait–based rather than from a behavioral perspective. In this study of small firms in the United Kingdom, we explored the relationships among managerial behaviors (based upon a competence model), entrepreneurial style (based on Covin and Slevin's theory), and firm type (in terms of sales growth performance). Principal components analysis of a management competence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
193
0
29

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(244 citation statements)
references
References 27 publications
(29 reference statements)
10
193
0
29
Order By: Relevance
“…Although growth is perceived to be an important characteristic of entrepreneurial behaviour (Sadler-Smith et al 2003), the actual process of growth is recognised to be complex and one which needs further investigation, particularly in theoretical terms ). We argue that controversies about the essence and definition of theoretical concepts may be in part due to the differences in metaphors used.…”
Section: Concluding Discussion -Re-imagining the Growth Processmentioning
confidence: 99%
“…Although growth is perceived to be an important characteristic of entrepreneurial behaviour (Sadler-Smith et al 2003), the actual process of growth is recognised to be complex and one which needs further investigation, particularly in theoretical terms ). We argue that controversies about the essence and definition of theoretical concepts may be in part due to the differences in metaphors used.…”
Section: Concluding Discussion -Re-imagining the Growth Processmentioning
confidence: 99%
“…According to McClelland (1973), when considering the provision of an intervention, the competency approach is vital because it is able to reduce the bias in the traditional personality traits approach. Despite the advantages of this approach, however, a caveat to the general endorsement of the competency model of the entrepreneurial success has been identified (Sadler-Smith et al 2003). They point out that research so far does not distinguish between entrepreneurial competencies and managerial competencies.…”
Section: The Competency Approachmentioning
confidence: 99%
“…According to D.C McClelland (1973), when considering the provision of an intervention, the competency approach is vital because of its capability to reduce the prejudice of the traits approach. Notwithstanding the benefits of this approach, however, a limitation to the competency model has been identified (Sadler-Smith et al 2003). They point out that research so far has shown no differentiation between entrepreneurial competencies and managerial competencies.…”
Section: The Competency Approachmentioning
confidence: 99%